A flow bioreactor system compatible with real-time two-photon fluorescence lifetime imaging microscopy. (1st February 2018) - Shen, Nian; Riedl, Julia A; Carvajal Berrio, Daniel A; Davis, Zachary; Monaghan, Michael G; Layland, Shannon L; Hinderer, Svenja; Schenke-Layland, Katja
Abstract: Bioreactors are essential cell and tissue culture tools that allow the introduction of biophysical signals into in vitro cultures. One major limitation is the need to interrupt experiments and sacrifice samples at certain time points for analyses. To address this issue, we designed a bioreactor that combines high-resolution contact-free imaging and continuous flow in a closed system that is compatible with various types of microscopes. The high throughput fluid flow bioreactor was combined with two-photon fluorescence lifetime imaging microscopy (2P-FLIM) and validated. The hydrodynamics of the bioreactor chamber were characterized using COMSOL. The simulation of shear stress indicated that the bioreactor system provides homogeneous and reproducible flow conditions. The designed bioreactor was used to investigate the effects of low shear stress on human umbilical vein endothelial cells (HUVECs). In a scratch assay, we observed decreased migration of HUVECs under shear stress conditions. Furthermore, metabolic activity shifts from glycolysis to oxidative phosphorylation-dependent mechanisms in HUVECs cultured under low shear stress conditions were detected using 2P-FLIM. Future applications for this bioreactor range from observing cell fate development in real-time to monitoring the environmental effects on cells or metabolic changes due to drug applications.